Kontribusi Pendidikan Agama Islam dalam Pembentukan Moral dan Etika Siswa di Indonesia - Elva Rahayu; Ehwanudin Ehwanudin; Kus Hendar (KURAS Institute, 2024)
This research aims to examine the influence of Islamic Religious Education (PAI) on the ethics and morals of students at SDN 02 Lempuyang Bandar, Indonesia. Employing a qualitative methodology, the study gathered data through documentation, interviews, and observations. The analysis of the data was conducted through three primary steps: data reduction, data presentation, and conclusion drawing. The findings reveal that Islamic Religious Education significantly contributes to the development of students’ values, including faith, integrity, self-control, accountability, and patriotism. However, the overall effectiveness of this education is limited by a less supportive social environment and a lack of varied teaching methods. To nurture morally conscious students who have a love for their country, it is crucial to adopt innovative teaching strategies in Islamic Religious Education and to promote strong collaboration among the community, families, and schools. This research contributes to the discourse surrounding children's moral development through a value-based education approach, highlighting that Islamic Religious Education should not only be viewed as a cognitive subject but also as a vital tool for character transformation and the fostering of noble qualities from an early age.